Propagation of Polyscias guilfoylei in substrate based on decomposed babassu stem and carbonized rice husk (Research, Society and Development, 2020)
The vegetative propagation of flowering plants by cuttings is a viable alternative for large-scale production, and when associated with regional substrates, this alternative makes it possible to obtain seedlings that meet the demands of the consumer market, in addition to reducing production costs. It was sought to evaluate with the research, increasing proportions of decomposed babassu stem (CDB), plus carbonized rice husk (CAC) in the vegetative propagation of Polyscias guilfoylei. The experiment was conducted in a greenhouse with 70% light interception between August and October 2019. A completely randomized design was used, with six treatments in the following proportions: 100% CAC; 20% CDB + 80% CAC; 40% CDB + 60% CAC; 60% CDB + 40% CAC; 80% CDB + 20% CAC; 100% CDB. The variables were: number of leaves; leaf area; number of shoots; sprouting height; sprouting diameter; root length; root volume; fresh mass of the aerial part; fresh root mass; aerial part dry mass; dry root mass; pile diameter; survival percentage and Dickson's quality index. After 60 days it was found that it is not interesting to produce seedlings of P. guilfoylei in the proportions of 100% CAC and 100% CDB. However, the Polyscias guilfoylei stems responded positively when using the proportions of 60% CDB + 40% CAC and 80% CDB + 20% CAC, these proportions being recommended.